Seeing the forest and the trees : human-environment interactions in forest ecosystems - Moran, Emilio F.; Ostrom, Elinor (Mit Press, 2005)
'Seeing the Forest and the Trees' examines changes in land cover & land use in forested regions as major contributors to global environmental change.